Mizaj assessment and data analysis methods in Amirkola health and aging project (AHAP cohort) - Morteza Mojahedi; Roshanak Saghebi; Nargess Gorji; Reihaneh Moeini; Seyed Reza Hosseini; Ali Bijani; Reza Ghadimi; Seyyed Ali Mozaffarpur; Hoda Shirafkan (Babol University of Medical Sciences, 2022)
Background: One of the principles of Persian medicine (PM) is the individualized approach that is presented with the concept of Mizaj. In this viewpoint, Mizaj is determined for every person based on 10 criteria, which is a result of the Mizaj of the main organs, including the brain, liver, and heart. There is no standard diagnostic tool for Mizaj assessment in the elderly. The purpose of this study is to explain the method of Mizaj assessment and data analysis in the elderly in the second phase of the Amirkola health and aging project (AHAP) in Iran. Methods: In this study, a novel Mizaj assessment method in two phases is presented. In the first phase, 1541 elderly were assessed by a PM expert and typical diagnoses were determined. At the second phase, an expert panel including 5 PM experts evaluated the cases. The paraclinical and metric data of the elderly whose Mizaj agreed in the expert panel was used to assess its correlation with Mizaj. Conclusion: In the lack of valid and reliable questionnaires to assess the personalized viewpoint of PM, a new expert-based method has been introduced that can be used in similar studies. The result of the Mizaj assessment in this way will be used to obtain objective values for the Mizaj assessment.